Management of obstructive sleep apnea in pediatric craniofacial anomalies - Rachmiel, Adi (Medknow Publications & Media Pvt Ltd, 2012)
INTRODUCTION: Obstructive sleep apnea (OSA) is often associated with congenital craniofacial malformations such as Pierre-Robin Syndrome, Hemifacial Microsomia, Treacher Collins Syndrome resulting in decreased pharyngeal airway, which, in severe cases, leads to tracheostomy dependence. Some pediatric patients had tracheostomies done and others with severe respiratory distress were considered tracheostomy candidates. MATERIALS AND METHODS: Twelve patients with severe respiratory distress without tracheostomy and ten patients with tracheostomy were treated by mandibular distraction osteogenesis using either external or internal devices. The expansion of mandibular framework was analyzed using bony cephalometric landmarks and computed tomography (CT). RESULTS: The results demonstrated average mandibular elongation of 29 mm on each side using the external devices and 22 mm using the internal devices, and an increase in mandibular volume and pharyngeal airway. The group of patients with tracheostomies were decannulated and in the patients with respiratory distress there was improved airway with improvement of signs and symptoms of OSA with elimination of oxygen requirement. CONCLUSIONS: Mandibular distraction is a useful method in younger children with OSA expanding the mandible and concomitantly advancing the base of tongue and hyoid bone increasing the pharyngeal airway. The external devices permit greater distraction length, the removal is simple but the devices are uncomfortable for the patients. On the other hand, the internal devices are more comfortable for patients but permit shorter distraction length and require a second operation for removal.